Utilization of Papaya Seeds as an Ingredient for Making Environmentally Friendly Insecticides Against Sangit Weed - Khakam Ma’ruf; Annisa 'Amali Shoolihah; Darmono; Bagus Putra Setiyawa; Yanuar Agung Fadlullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Papaya (Carica Papaya) is a plant that is often found in tropical areas, one of which is in Indonesia. Inside the papaya seeds there is a karpain content, the karpain content is able to eradicate the stink bug pest that usually attacks papaya plants. This study used an experimental method in which this method tested the karpain content in papaya seeds. Making a bioinsecticide formula with a ratio of 25 ml and 75 ml; 50 ml and 50 ml and 75 ml and 25 ml. based on research and analysis of field data from the trial results showed that papaya seed extract (Carica papaya) at doses of 25%, 50%, 75%, and 100% had an effect on the death of walang sangit so that the higher the carpain content in papaya seeds, the more effective at eradicating insecticides.